Diagnosis of rare bleeding disorders. (6th May 2022) - Meijer, Karina; van Heerde, Waander; Gomez, Keith
Abstract: Rare bleeding disorders result in significant morbidity but are globally underdiagnosed. Advances in genomic testing and specialist laboratory assays have greatly increased the diagnostic armamentarium. This has resulted in the discovery of new genetic causes for rare diseases and a better understanding of the underlying molecular pathology. Abstract :